Recent advances in the catalytic hydroboration of carbonyl compounds. Issue 13 (12th June 2019) - Shegavi, Mahadev L.; Bose, Shubhankar Kumar
Abstract : The latest development in the catalytic hydroboration of CO groups is summarized in this review. Access to borate ester intermediates provides a pathway to convert them into the corresponding valuable functionalized alcohols. Abstract : The chemoselective catalytic hydroboration of aldehydes and ketones has found widespread applications in organic chemistry due to the synthetic utility of borate ester intermediates, and more importantly their conversion into corresponding functionalized alcohols under mild reaction conditions provides significant safety advantages over the use of hazardous metal hydrides and harsh conditions in catalytic hydrogenation processes. Most of the catalytic systems developed for such transformations employ mainly precious metals, main-group elements and rare earth metals as catalysts. This article summarizes recent advancements in substrate scope and discovery of new catalyst systems including the use of non-precious metals and reusable/heterogeneous catalyst systems for the hydroboration of carbonyl compounds. We will also present the mechanistic studies of these catalytic reactions.